Vaccination sequence effects on immunological response and tissue bacterial burden in paratuberculosis infection in a rabbit model. (December 2016) - Arrazuria, Rakel; Molina, Elena; Garrido, Joseba; Pérez, Valentín; Juste, Ramón; Elguezabal, Natalia
Abstract Paratuberculosis (PTB), a chronic granulomatous enteritis produced byMycobacterium avium subspeciesparatuberculosis (MAP), is considered as one of the diseases with the highest economic impact in the ruminant industry. Vaccination against MAP is recommended during the first months after birth on the basis that protection would be conferred before the first contact with mycobacteria. However, little is known about the therapeutic effect of MAP vaccination in controlled experimental conditions. The current study was designed to evaluate the efficacy of vaccination before and after challenge with MAP in a rabbit infection model. The rabbits were divided into four groups: non-infected control (NIC, n  = 4), infected control challenged with MAP (IC, n  = 5), vaccinated and challenged 1 month after with MAP (VSI, n  = 5) and challenged with MAP and vaccinated 2 months later (IVS, n  = 5). The results from this study show a quick increase in IFN-γ release upon stimulation with bovine, avian and johnin PPD in animals vaccinated before MAP challenge. All vaccinated animals show an increased humoral response as seen by western blot and ELISA. The final bacteriology index (considering tissue culture and qPCR) shows that the IC group was the most affected. Vaccination after infection (IVS) produced the lowest bacteriology index showing significant differences with the IC group (p  = 0.034). In conclusion, vaccination against MAP shows positive effects in a rabbit model. However, vaccination after infection shows a slightly stronger protective effect compared to vaccination before infection, suggesting a therapeutic effect. This feature could be applied to previously infected adult animals under field conditions.